1995
DOI: 10.1159/000239372
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Therapy and Prophylaxis with Cotrifazid, a Multiple Complex Combination Consisting of Rifampicin + Isoniazid + Sulfamethoxazole + Trimethoprim

Abstract: This report contains the first therapeutic results with the multiple combination rifampicin + isoniazid + sulfamethoxazole + trimethoprim in the treatment of malaria. Clinical symptoms declined rapidly and parasites were cleared from the erythrocytes. Tolerance was excellent. This fixed combination is outstandingly practicable, with few problems with compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The reasons for use of CF in the treatment of malaria tropica was based exclusively on empiric data reported in 1995/1996 [5,6]. These investigators reported previously for CF positive therapeutic results in tuberculosis, leprosy and chronic Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for use of CF in the treatment of malaria tropica was based exclusively on empiric data reported in 1995/1996 [5,6]. These investigators reported previously for CF positive therapeutic results in tuberculosis, leprosy and chronic Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators reported previously for CF positive therapeutic results in tuberculosis, leprosy and chronic Salmonella sp. carriers [6]; they postulated a 'synergism' between CF components [19] and stressed the need for a fixed combination, particularly for low-income countries [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical picture improves quickly [7], In a few days, the erythrocytes become com pletely negative (free of parasites; tables 2-4).…”
Section: Cotrifazid In Malariamentioning
confidence: 99%
“…In the context of this wide-ranging research program utilizing the experience with other disease (leprosy, tuberculosis, leishmaniasis, salmonellosis), Cotrifazid in the following combination (table l) [6] was used in Malawi [7] in nonpretreated Plasmodium falciparum cases (malaria tropica) and in cases pretreated in vain with Fansidar, quinine or chloroquine.…”
Section: Cotrifazid In Malariamentioning
confidence: 99%